Pressure in the spotlight: effects of monitoring pressure and outcome pressure on time-sharing performance - Pennanen, Niki; Oksama, Lauri (Springer Nature, 2026)
Performing under pressure, particularly in multitasking environments, is a critical challenge in both everyday life and high-stakes professions. This study investigated the differential effects of monitoring and outcome pressure on time-sharing performance and allocation of visual attention. Using a within-subjects design, 30 participants completed a recently devised time-sharing task requiring prioritization under three different pressure conditions. We hypothesized that in a high-demand time-sharing environment, outcome pressure would impair task performance and visual sampling of subtasks more than monitoring pressure. To investigate, we recorded participants’ task performance metrics and eye movements. However, our confirmatory analyses found no evidence supporting either hypothesis. In contrast, our additional exploratory analyses revealed that monitoring pressure, not outcome pressure, led to a statistically significant performance decrease. Notably, this effect occurred without changes in visual sampling. This unexpected finding reflects the high sensorimotor demands of the task, specifically the need for precise and rapid mouse movements, which may have been disrupted by the participants’ heightened self-consciousness under monitoring pressure. Our findings contribute to the literature on the differential effects of monitoring and outcome pressure, with potential implications for high-stakes domains like military operations. In situations requiring fine motor control—such as piloting aircraft or operating drones—monitoring pressure may disrupt performance, even without altering attentional allocation. Similarly, everyday activities like driving under observation (e.g., driving tests) or performing in front of an audience may be affected. Understanding how pressure disrupts performance in such scenarios can inform training and support strategies to mitigate its impact.